Silencing LncRNA PVT1 Reverses High Glucose-Induced Regulation of the High Expression of PVT1 in HRMECs by Targeting miR-128-3p - Wang, Xuyang; Chen, Wangling; Lao, Wei; Chen, Yunxin (Hormone and Metabolic Research, 2022)
This paper aims to discuss the possibility of lncRNA PVT1 as a diagnostic biomarker for diabetic retinopathy (DR) and explore the underlying mechanism. Real-time quantitative polymerase chain reaction (RT-qPCR) was selected to determine the expression level of lncRNA PVT1 in the serum of all subjects. The receiver operating characteristic (ROC) curve reflected the diagnostic significance of PVT1 for DR patients. The Cell Counting Kit-8 (CCK-8) and Transwell assays were used to evaluate the effect of PVT1 expression on the proliferation and migration of human retinal microvascular endothelial cells (HRMECs). The luciferase reporter gene was selected to verify the interaction between PVT1 and miR-128-3p. The relative expression level of PVT1 in serum was higher in both the DB and DR group than in the healthy controls group (HC), and it was highest in the DR group. ROC curve indicated that serum PVT1 could distinguish between HC and DB patients, DB patients and DR patients, respectively. In vitro, high glucose induction significantly increased the proliferation and migration capabilities of HRMECs, but silencing PVT1 (si-PVT1) downregulated the proliferation and migration capabilities of HRMECs. The detection of luciferase reporter gene showed that lncRNA PVT1 targeted miR-128-3p, and there was a negative correlation in the serum of DR patients. In conclusion, this study confirmed that lncRNA PVT1 might regulate the process of DR by targeting miR-128-3p, and has the potential as a biomarker for the diagnosis of DR.
Keywords: diabetic retinopathy; lncRNA PVT1; miR-128-3p; diagnosis; high glucose